Subconjunctival Haemorrhage treated with Homoeopathy: A Case Report - Pal, Partha Pratim (Homœopathic Links, 2022)
Scratches, abrasions, lacerations, bruising and haemorrhages are some of the most commonly seen injuries of the eye, which respond well to homoeopathic medication. The following case study is an evidence-based illustration of such response.
Keywords: conjunctiva; haemorrhage; Arnica